Baclofen-induced pancreatitis - Nicolas Nassif; Nadia Katrib; Karam Karam; Elias Fiani (European Journal of Case Reports in Internal Medicine)
Acute pancreatitis is an inflammatory condition of the pancreas that can result from various aetiologies, one of them being drug-induced pancreatitis, a relatively rare cause. Drug-induced pancreatitis should be considered in patients presenting with epigastric pain, elevated pancreatic enzymes, and imaging findings consistent with acute pancreatitis, in the absence of any common precipitants such as alcohol, gallstones, trauma. We report a case of acute pancreatitis following the initiation of baclofen therapy, with no other identifiable risk factors. A probable drug adverse reaction was established through the Naranjo Adverse Drug Reaction Probability Scale. This case highlights the need for physicians to consider baclofen as a potential cause of acute pancreatitis.